(untitled) (Perner’s Contacts, 2012)
This paper deals with the development of container vessels. There are described key elements of each class vessels as well as the other important parameters and technological equipments. The attention is also concerned to development of the most contemporary capacity class container vessel, which bring completly new conception of container vessels. In the end is analysed access to the ports, circulation of vessels among the ports, sailing lists etc.